Effect of Solar Chimney and PCM cooling ceiling to the air flow inside a naturally-ventilated building. (March 2019) - Suhendri,
Abstract: Computational fluid dynamics (CFD) gives significant contributions to building design fields. Building ventilation is the most common problem to simulate in CFD software. 2D and 3D simulation can be used to simulate cross ventilation within the building. ANSYS Fluent is commonly used CFD software, and it has been used in this study to assess the environment of an atrium building under buoyancy-driven natural ventilation and wind-driven natural ventilation. Buoyancy is one of the main forces driving flows. Buoyancy effect happened when the moving fluid is lighter or heavier than surrounding fluid. This paper will elaborate the use of ANSYS Fluent in assessment the environmental performance of a building. Some cases on a building were set in this study. The aim is to simulate accurately buoyancy-driven air flow inside a building for natural ventilation, visualize and analyse simulation results, provide architectural/engineering solution to natural ventilation of buildings. Cooler air appears from ceilings and creates cooling to the room down. Meanwhile, solar chimney generates wind flow across the building due to temperature differences within the chimney.